2016
DOI: 10.1109/lgrs.2016.2532743
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Vascular Plant Richness in a Heterogeneous Wetland Using Spectral and Textural Features and a Random Forest Algorithm

Abstract: A method to predict vascular plant richness using spectral and textural variables in a heterogeneous wetland is presented. Plant richness was measured at 44 sampling plots in a 16-ha anthropogenic peatland. Several spectral indices, first-order statistics (median and standard deviation), and second-order statistics [metrics of a gray-level co-occurrence matrix (GLCM)] were extracted from a Landsat 8 Operational Land Imager image and a Pleiades 1B image. We selected the most important variables for predicting r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Regarding the textural metrics, Laurin et al [24] in the Gola Rainforest National Park, obtained good predictions (R 2 = 0.84) using these type of metrics to estimate diversity based on hyperspectral data. Species richness predictions, using textural predictors, were reported by Cabezas et al [19] in an anthropogenic peatland divided into two zones with different types of management: productive (with Sphagnum extraction) and conservation (corresponding to peatland P2 in this study). In summary, spatial resolution of the scenes seems to be important for the analysis, especially in peatlands.…”
Section: Satellite Sensor Comparisonmentioning
confidence: 54%
See 2 more Smart Citations
“…Regarding the textural metrics, Laurin et al [24] in the Gola Rainforest National Park, obtained good predictions (R 2 = 0.84) using these type of metrics to estimate diversity based on hyperspectral data. Species richness predictions, using textural predictors, were reported by Cabezas et al [19] in an anthropogenic peatland divided into two zones with different types of management: productive (with Sphagnum extraction) and conservation (corresponding to peatland P2 in this study). In summary, spatial resolution of the scenes seems to be important for the analysis, especially in peatlands.…”
Section: Satellite Sensor Comparisonmentioning
confidence: 54%
“…This can turn into a major problem in the validation process, when the bootstrap method is implemented and sub-samples are chosen, reducing the input observations used in the model. In spite of these limitations, studies using RF to predict species richness obtained accurate predictions with similar field samples as the one used in this study [19,24], and demonstrated to be an important tool for modeling α-diversity. This study shows that both GLM and RF are valid methods for predicting α-diversity with similar performance; nonetheless, according to Latifi et al [21] and Lopatin et al [33], GLM proved to be a more parsimonious approach, since it was easier to interpret, required less computation time, and fewer predictors.…”
Section: Model Comparisonsmentioning
confidence: 90%
See 1 more Smart Citation
“…Specifically, variation and heterogeneity in spectral reflectance increased with increasing Shannon diversity among plots. Increasing spectral heterogeneity has been previously used as a proxy for diversity in studies that have mapped peatland ecological diversity using remote sensing [91][92][93]. This type of study is based on the species-area relationship in which species richness increases with scale across a heterogeneous landscape [94].…”
Section: Remote Sensing Of Boreal Peatland Species Diversitymentioning
confidence: 99%
“…The Grey Level Co-occurrence Matrix (GLCM) is a commonly used method of analyzing texture and has proven an effective approach when applied to vegetation classification [14,15]. Based on GLCM's popularity in vegetation classification, some researchers [16,17] have attempted to classify wetland vegetation using texture obtained from the approach. Berberoglu et al [18] studied the land-use/cover change dynamics of a Mediterranean coastal wetland based on extraction of vegetation from Landsat TM images using GLCM.…”
Section: Introductionmentioning
confidence: 99%